2003
DOI: 10.1021/ma025776u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Semicrystalline Morphology on the Physical Aging Characteristics of Poly(phenylene sulfide)

Abstract: We report on the influence of semicrystalline morphology on the physical aging characteristics of poly(phenylene sulfide) or PPS. Specifically, the semicrystalline morphology of PPS was described in terms of a three-phase system comprising a crystalline phase, a mobile-amorphous phase, and a rigidamorphous phase. The physical aging kinetics were observed to depend on the relative amounts of the mobile-amorphous and rigid-amorphous phases, with accelerated aging rates measured in specimens with higher rigid-amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…At the measured bulk , the material is approaching thermodynamic equilibrium. Nevertheless, as stated in Struik (1987a, 1987b, 1989a, 1989b), Krishnaswamy et al (2003), and Vlasvelda et al (2005), in semi-crystalline materials, aging can persist even at temperatures above bulk . The fact that the obtained for both materials were nearly the same up till approximately 50 °C, and then diverged can possibly be attributed to the difference in the in the interphasial region presented in the AR-CF/PPS system.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…At the measured bulk , the material is approaching thermodynamic equilibrium. Nevertheless, as stated in Struik (1987a, 1987b, 1989a, 1989b), Krishnaswamy et al (2003), and Vlasvelda et al (2005), in semi-crystalline materials, aging can persist even at temperatures above bulk . The fact that the obtained for both materials were nearly the same up till approximately 50 °C, and then diverged can possibly be attributed to the difference in the in the interphasial region presented in the AR-CF/PPS system.…”
Section: Resultsmentioning
confidence: 91%
“…In semi-crystalline polymers, Struik (1987a, 1987b, 1989a, 1989b), Krishnaswamy et al (2003) and Vlasvelda et al (2005) have shown that physical aging process still remains at temperatures well above the measured bulk of the polymeric material. An explanation for this extended temperature window involves a range of different amorphous phases, in which molecular and segmental mobilities depend upon their proximity to a rigid crystalline region.…”
Section: Introductionmentioning
confidence: 99%
“…resulting in higher nucleation density and smaller spherulitic structures. It is also known that a semicrystalline morphology with higher degree of constraint on the amorphous region may form at crystallization condition of low chain mobility and high nucleation density [17]. Thus, much less mobility of the amorphous phase in 50MC is expected, leading to the negligible bond strength developed over the interface.…”
Section: Bond Strengthmentioning
confidence: 99%
“…Furthermore, polymers in the semicrystalline state also have nanoconfined amorphous regions that can be either rigid amorphous [Menczel and Wunderlich, 1981] or simply confined or constrained [Struik, 1987a[Struik, ,b, 1989aWunderlich, 1994;Aharoni, 1998], depending on the view that one takes. Aging of such confined systems has been little studied, although some thoughtful results were found early with measurements of aging of the rigid amorphous phase [Menczel and Wunderlich, 1981;Huo and Cebe, 1992;Wunderlich, 1994;Krishnaswamy et al, 2003] in semicrystalline polymers and simply the aging of semicrystalline polymers in the broadened glass transition regime of the constrained amorphous phase [Struik, 1987a[Struik, ,b, 1989aBeckmann et al, 1997]. More recent work on nanocomposites has suggested that aging can be suppressed by making the nanoparticles attractive [Priestley et al, 2007c], which can also increase the glass transition temperature.…”
Section: Physical Aging and Structural Recovery At The Nanoscalementioning
confidence: 99%